Primary school teachers’ views of the use of gender-neutral language to enhance gender equality in schools - Richard Nyika; Tambawoga Chriswell Muchena (MSU Press, 2023)
Language plays an important role in shaping, and directing behaviour. Feminists argue that the use of gendered language has consequences for relations, and relative status of male and female learners in the education system because it is used to maintain, and reinforce sexism. Language can, therefore, be used to influence gender status. Schools are linguistic environments flooded with gendered language that can influence the development of gender roles. Teachers as key players in this environment play a very important role in cultivating gender equality values through using, and teaching, gender-neutral language. This study explores views by primary school teachers on the use and teaching of gender-neutral language as another frontier that can be used to promote gender equality values. The study is a descriptive survey which used questionnaires and interviews to collect data from 30 randomly sampled primary school teachers in Gweru urban district (Zimbabwe). The results showed that most teachers were not aware that a language is a strong tool which can be effectively used to influence gender equality. However, they supported the use of gender-neutral language as an effective tool in promoting gender equality. The study recommended that teachers should be exemplary in their use of gender-neutral language, and should encourage learners to use gender-neutral language. It is further recommended that gender-neutral language should be a component of language teaching in schools and that primary school textbooks should also be conscious of gender-neutral language too.